Integration Strategy of Cyber Defense with National Cyber Security to Maintain State Sovereignty - Andi Sutomo; Amarulla Octavian; Pujo Widodo; Yono Reksoprodjo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Threats to state sovereignty are becoming increasingly complex as technology develops rapidly. In order to overcome this incident, a national cyber system is needed which consists of cyber security, cyber defense, and other types of cyber with their main duties and functions in practice, preventive measures, prosecution, and so on to law enforcement as an effort to protect cyber ecosystems and assets. Vital from attacks through cyberspace (cyber attacks) that aim to disrupt the confidentiality, integrity, authentication, and availability of data and information. The paradigm of national security which has shifted to become more complex, including guaranteeing the privacy of every citizen, encourages the main obligation of a country to provide privacy protection from cyber-attack. The qualitative approach method used in this research is explanatory qualitative. The data used in this research is secondary data in the form of a literature study, by looking for various literature that is in accordance with the discussion on Strategy for Integration of Cyber Defense with Cyber Security Nationally to Maintain State Sovereignty. The current condition of cyber defense can be described based on aspects of Policy, Institutions, Technology and supporting infrastructure, and Human Resources (HR).